2020
DOI: 10.1128/aac.01516-19
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Fungemia in Greece with a Focus on Candidemia during the Recent Financial Crisis: a 10-Year Survey in a Tertiary Care Academic Hospital and Review of Literature

Abstract: Updated information on the epidemiology of candidemia, particularly during severe socioeconomic events, is important for proper management of these infections. A systematic literature review on candidemia in Greece and a retrospective surveillance study were conducted in a tertiary university hospital during the years of the recent financial crisis (2009 to 2018) in order to assess changes in incidence rates, patient characteristics, species distribution, antifungal susceptibilities, and drug consumption. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
49
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 63 publications
8
49
6
1
Order By: Relevance
“…Our data showed that the median age of patients with candidaemia and the proportion of males were similar to those in other studies [ 8 , 18 23 ]. Moreover, our study showed that the patients with candidaemia were hospitalised mostly in internal medicine wards, which is different from other studies that reporting hospitalisation mainly in ICU wards [ 8 , 22 , 24 27 ], but similar to other studies [ 28 31 ]. This phenomenon may be related to the demographic characteristics of the inpatients in our hospital, most of whom had more than two underlying diseases and were hospitalised in internal medicine wards.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data showed that the median age of patients with candidaemia and the proportion of males were similar to those in other studies [ 8 , 18 23 ]. Moreover, our study showed that the patients with candidaemia were hospitalised mostly in internal medicine wards, which is different from other studies that reporting hospitalisation mainly in ICU wards [ 8 , 22 , 24 27 ], but similar to other studies [ 28 31 ]. This phenomenon may be related to the demographic characteristics of the inpatients in our hospital, most of whom had more than two underlying diseases and were hospitalised in internal medicine wards.…”
Section: Discussioncontrasting
confidence: 99%
“…This phenomenon may be related to the demographic characteristics of the inpatients in our hospital, most of whom had more than two underlying diseases and were hospitalised in internal medicine wards. However, the incidence of candidaemia was still the highest in the ICU, similar to other studies [8,[30][31][32][33][34]. In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of MY found in Spain (2.4%) was slightly higher than a previous study, which detected a rate of 1.8% [ 12 ]. Other studies carried out in tertiary care hospitals in Germany and Greece have detected rates of MY of 4.4% and 4.7% [ 17 , 18 ], consistent with the rates detected in this study (4.9% and 5%, respectively). In contrast, in Poland, a multicenter survey in patients with candidemia detected a lower proportion of MY infections (3.5% vs. 6.4% found in this study) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon may be related to the demographic characteristics of the inpatients in our hospital, most of whom had more than two underlying diseases and were hospitalized in internal medicine wards. However, the incidence of candidaemia was still the highest in the ICU, similar to other studies [8,[30][31][32][33][34]. In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C.…”
Section: Discussionsupporting
confidence: 90%
“…Our data showed that the median age of patients with candidaemia and the proportion of males were similar to those in other studies [8,[18][19][20][21][22][23]. Moreover, our study showed that the patients with candidaemia were hospitalized mostly in internal medicine wards, which was different from other studies that reported hospitalisation in mainly ICU wards [8,22,[24][25][26][27], and similar to other studies [28][29][30][31]. This phenomenon may be related to the demographic characteristics of the inpatients in our hospital, most of whom had more than two underlying diseases and were hospitalized in internal medicine wards.…”
Section: Discussionsupporting
confidence: 84%